Mapping and Assessment of Degraded Land in the Heihe River Basin, Arid Northwestern China - Yumin Cai; Shanzhong Qi (Sensors, 2007)
Land degradation is a great threat in the Heihe River Basin, located in the aridinland of northwestern China and land desertification is one of the main aspects ofenvironmental changes in this basin. Previous studies have focused on water resourceutilization and soil erosion, but the status of degraded land in the Heihe River Basin, suchas its distribution, extent and precise characteristics is often inadequately known. Based onfield observations and TM images from the year 2003, this study provides classificationand evaluation information concerning the degraded land in the basin of the Heihe River.There are five types of degraded land types in the Heihe River Basin: water eroded in thesouthern mountains, sandified and vegetation degraded near the oases, aridized in the lowreaches, and salinized in the lowlands. The total degraded area covers 29,355.5 km2,22.58% of the land in the study area. Finally, degraded land in the Heihe River Basin wasevaluated according to changes in the physical structure and chemical components of soils,land productivity, secondary soil salt, and water conditions.